Methylation analysis of p16, SLIT2, SCARA5, and Runx3 genes in hepatocellular carcinoma. Issue 41 (October 2017) - Sun, Gaofeng; Zhang, Chen; Feng, Min; Liu, Wensheng; Xie, Huifang; Qin, Qin; Zhao, E.; Wan, Li
Abstract : Abstract: This study is to investigate the methylation status of multiple tumor suppressor 1 ( p16 ), secreted glycoprotein 2 ( SLIT2 ), scavenger receptor class A, member 5 putative ( SCARA5 ), and human runt-related transcription factor 3 ( Runx3 ) genes in the peripheral blood of hepatocellular carcinoma (HCC). This is a case–control study. The peripheral blood samples were collected from 25 HCC patients, 25 patients with high risk of HCC (defined as "internal control group"), and 25 healthy individuals (defined as "external control group"), respectively. Then the methylation status of p16, SLIT2, SCARA5, and Runx3 genes in the blood samples were analyzed by pyrosequencing. The relationship between the methylation and the clinical features of HCC patients were evaluated. The methylation levels in the 7 CpG loci of p16 gene in HCC patients were low and without statistically significant difference ( P  > .05) compared to the control groups. Although the methylation levels of CpG3 and CpG4 in SLIT2 gene loci were higher than those of the control groups, there was no statistically significant difference ( P  > .05). However, the methylation rate of CpG2 locus in SCARA5 gene in HCC patients was significantly higher ( P  < .05). And the methylation rates of CpG1, CpG2, CpG3, CpG4, CpG5, and CpG8 in Runx3 gene in HCC patients were significantly different to that of control groups ( P  < .05). We also have analyzed the correlations between the CpG islands methylation of Runx3 or SCARA5 genes and the age, gender, hepatitis B, liver cirrhosis, alpha fetal protein, or hepatitis B surface antigen (HBsAg) of the HCC patients, which all showed no significant correlations ( P  > .05). The methylation status of SCARA5 and Runx3 genes are abnormal in HCC patients, which may further be used as molecular markers for early auxiliary diagnosis of liver cancer.